Genome Wide Identification and Expression Profiling of SWEET Genes Family Reveals Its Role During Plasmodiophora brassicae-Induced Formation of Clubroot in Brassica rapa - Li, Hong; Li, Xiaonan; Xuan, Yuanhu; Jiang, Jing; Wei, Yangdou; Piao, Zhongyun (Frontiers in Plant Science, 2018)
Plasmodiophora brassicae is a soil borne pathogen and the causal agent of clubroot, a devastating disease of Brassica crops. The pathogen lives inside roots, and hijacks nutrients from the host plants. It is suggested that clubroot galls created an additional nutrient sink in infected roots. However, the molecular mechanism underlying P. brassicae infection and sugar transport is unclear. Here, we analyzed sugar contents in leaves and roots before and after P. brassicae infection using a pair of Chinese cabbage near-isogenic lines (NILs), carrying either a clubroot resistant (CR) or susceptible (CS) allele at the CRb locus. P. brassicae infection caused significant increase of glucose and fructose contents in the root of CS-NIL compared to CR-NIL, suggesting that sugar translocation and P. brassicae growth are closely related. Among 32 B. rapa SWEET homologs, several BrSWEETs belonging to Clade I and III were significantly up-regulated, especially in CS-NIL upon P. brassicae infection. Moreover, Arabidopsis sweet11 mutant exhibited slower gall formation compared to the wild-type plants. Our studies suggest that P. brassicae infection probably triggers active sugar translocation between the sugar producing tissues and the clubbed tissues, and the SWEET family genes are involved in this process.